Gangrenous Cecal Volvulus Complicating Puerperium: Is the Delay in Diagnosis Really Inevitable? - Chanderdeep Sharma; Shashank Shekhar; Satish Kumar; Rajesh Chaudhary (Hindawi Limited, 2012)
Volvulus in puerperium is a rare event. We present a case of cecal volvulus following normal vaginal delivery that ended with cecal gangrene and hemicolectomy.